Atividade alelopática dos extratos fresco e seco de folhas de barbatimão (Stryphnodendron adstringens (Mart.) Coville) e pata-devaca (Bauhinia forficata link) sobre a germinação e desenvolvimento inicial de plântulas de tomate - Manoel, Daniel Donini [UNESP]; Reis Doiche, Caio Fernando [UNESP]; Ferrari, Tairtara Bortolucci [UNESP]; Ferreira, Gisela [UNESP] (Universidade Estadual de Londrina (UEL), 2009)
The objective of this study aimed at the verification of the allelopatic action of extracts of "pata-de-vaca" (Bauhinia forficata Link) and "'barbatimao" (Stryhnodendron adsiringens (Mart.) Coville) on seeds of tomato (Lyeopersicum esculentum Mill). Tomato seeds placed in translucent "gerbox" were treated with aqueous extracts prepared with fresh and dry leaves of the tested species at the following concentrations: 100%, 75%, 50%, 25%, and 0% (control). The experimental design was completely randomized with five treatments and five replications of 25 seeds per plot per species. The data were submitted to the analysis of variance and the means compared by Tukey test at 5% of probability. Germination percentage, mean time and germination rates (MGT and MGR), and mean of the primary root length were evaluated. No difference was found for germination percentage of tomato seeds for the different extracts. For MGR, all treatments with fresh leaf extract differed from the check. MGT and MGR showed differences among the following dry leaf extracts concentrations: 25%, 75% and 100%. All treatments presented inhibitory effect on the length of the primary root.
Allelopathic activity of fresh and dry extracts of Stryphnodendron adstringens (Mart.) Coville and Bauhinia forficata link leaves on the germination and initial development of tomato seedlings
Keywords: Allelopathy; seeds; inhibition